2015 IEEE 7th International Conference on Cybernetics and Intelligent Systems (CIS) and IEEE Conference on Robotics, Automation 2015
DOI: 10.1109/iccis.2015.7274564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of using semi-autonomy features in mobile robotic telepresence systems

Abstract: Abstract-Mobile robotic telepresence systems used for social interaction scenarios require that users steer robots in a remote environment. As a consequence, a heavy workload can be put on users if they are unfamiliar with using robotic telepresence units. One way to lessen this workload is to automate certain operations performed during a telepresence session in order to assist remote drivers in navigating the robot in new environments. Such operations include autonomous robot localization and navigation to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“… 3. The Giraff robotic platform was used in previous works, such as Jaimez et al (2015), Melendez-Fernandez et al (2016), and Kiselev et al (2015), and from such experiences we concluded that a height 0.92 m is optimal for being able to see at a convenient distance both the objects on surfaces such as tables or counters and the objects on the floor. …”
mentioning
confidence: 88%
“… 3. The Giraff robotic platform was used in previous works, such as Jaimez et al (2015), Melendez-Fernandez et al (2016), and Kiselev et al (2015), and from such experiences we concluded that a height 0.92 m is optimal for being able to see at a convenient distance both the objects on surfaces such as tables or counters and the objects on the floor. …”
mentioning
confidence: 88%
“…Client applications will be extended with modular control components to conveniently support visitor operations. In line with the developments presented in the studies by Kiselev 33 and Gonzalez-Jimenez et al 36 at least, three default configurations will be considered: novice, expert, and technical user profiles. To that aim, we will address the design of an adequate test environment and convenient user studies, which is one of the most challenging and essential parts of our future work.…”
Section: Future Workmentioning
confidence: 99%
“…Most of the solutions found in the literature tackle robotic telepresence by relying on proprietary software (e.g. Skype or VSee) in combination with specific plugins to integrate robotic control commands, 33 which is the approach followed by Social Robot and GiraffPlus platforms. The strength of these solutions relies on the efficient management of networking, videoconference, and realtime communications provided by expert companies, but this strategy has several disadvantages when it comes to the design of features for research prototypes like the aforementioned.…”
Section: Related Workmentioning
confidence: 99%
“…Some drive the robot only manually, some use only the autonomous features, while others combine manual and autonomous driving. The implementation and evaluation of the second plug-in are further detailed in Kiselev, Kristoffersson, Melendez, et al (2015).…”
Section: Autonomous Navigationmentioning
confidence: 99%